TEACHING HISTORY STUDENTS BASED ON ACTIVITIES AND COMPETENCES IN CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) - Torebaeva, O.; Arzieva, B. (SCIENCE and SOCIETY, 2025)
This article introduces the concept of competences in the history of CLIL and presents a range of activities through collaborative methods that influence learners' subject and language knowledge. CLIL history is suggested to benefit from activities that emphasize the transfer of historical knowledge, improve reading and listening comprehension, and require students to produce a written product.